2021
DOI: 10.2147/pgpm.s274741
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Drug-Related Genes in Native Americans of the Brazilian Amazon

Abstract: Introduction: The genetic admixture of the Brazilian population has considerable relevance to the implementation of the principles of pharmacogenomics (PGx), as it may compromise the extrapolation of data obtained in more homogeneous world populations. Purpose: This study aims to investigate a panel of 117 polymorphisms in 35 pharmacogenes, which contains label recommendations or clinical evidence by international drug regulatory agencies, in Amazonian Native American populations, and compare the results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…When DNA is exposed to radiation, DNA double-strand breaks occur, which favors a response to this damage, such as cellular radioresistance [46,47]. This was the first exome study to examine genes associated with the response to radiotherapy in indigenous populations, a group that is usually underrepresented in genetic studies, especially in precision medicine [48].…”
Section: Discussionmentioning
confidence: 99%
“…When DNA is exposed to radiation, DNA double-strand breaks occur, which favors a response to this damage, such as cellular radioresistance [46,47]. This was the first exome study to examine genes associated with the response to radiotherapy in indigenous populations, a group that is usually underrepresented in genetic studies, especially in precision medicine [48].…”
Section: Discussionmentioning
confidence: 99%
“…However, some population groups remain underrepresented in these types of investigations, such as Native American populations. Recently, some efforts have been made to include genetic information about allelic frequencies of Native American populations and their influence on susceptibility to diseases, such as severe forms of COVID-19 [ 23 ], psychological disorders [ 24 ], oncological diseases [ 25 , 26 ], and also on different types of pharmacological treatments [ 12 , 13 , 27 , 28 ]. Most of these studies are focused on one or a few group of genes.…”
Section: Discussionmentioning
confidence: 99%
“…These populations are extremely underrepresented in genetic research. In parallel, some studies have already demonstrated that Amerindian groups have distinct genetic profiles concerning pharmacogenomic biomarkers widely used in clinical practice [ 12 , 13 ], which further reinforces the need for their inclusion in pharmacogenomic studies.…”
Section: Introductionmentioning
confidence: 94%